2019
DOI: 10.5812/semj.81106
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Study of Cryptosporidium with SSU-rRNA in Children Younger Than Ten Referring to Hospitals of Zabol, Southeast of Iran

Abstract: Background: Cryptosporidium parasite is the cause of human gastroenteritis and other cold and warm-blooded animals that have been widely distributed throughout the world. Genetic information on opportunistic pathogens in immunocompromised patients leads to an increase in the information on epidemiology, patient care, patient management, and rescue. In Iran, infection to Cryptosporidium spp. has been reported, yet only molecular genes can differentiate species and genotype discrimination of the cyst. The molecu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 16 publications
0
4
0
1
Order By: Relevance
“…This study has an ethical code zbmu.1.REC.1395.45 issued by the ethics committee of Zabol University of Medical science. This study is a continuation of our work on SSUrRNA that was published before in Shiraz E-Medical Journal 20 (16).…”
Section: Methodsmentioning
confidence: 54%
“…This study has an ethical code zbmu.1.REC.1395.45 issued by the ethics committee of Zabol University of Medical science. This study is a continuation of our work on SSUrRNA that was published before in Shiraz E-Medical Journal 20 (16).…”
Section: Methodsmentioning
confidence: 54%
“…As we can see, all three women are housewives and likely to be infected with dirty vegetables. Most of the infections in Iran are C. parvum (26)(27)(28). Molecular studies in the Middle East countries showed C. parvum, as the most dominant species in human infections (22) this is contrary to study of Squire and Ryan, which shows that C. hominis is the most cases of infection in Africa (27), detected C. hominis while none of the isolates in the present study were C. hominis.…”
Section: Discussionmentioning
confidence: 99%
“…Most of the infections in Iran are C. parvum (26)(27)(28). Molecular studies in the Middle East countries showed C. parvum, as the most dominant species in human infections (22) this is contrary to study of Squire and Ryan, which shows that C. hominis is the most cases of infection in Africa (27), detected C. hominis while none of the isolates in the present study were C. hominis. In contrary to our study, the other species of Cryptosporidium, C. meleagridis is one of the major human parasitic pathogens in African countries (29).…”
Section: Discussionmentioning
confidence: 99%
“…A nivel mundial, existen diversos estudios en donde ha sido posible la caracterización de Cryptosporidium a nivel de especie 15,24,32,[33][34][35] . No obstante, hasta donde conocemos, este es el primer reporte de las especies de Cryptosporidium circulantes en niños menores de cinco años de comunidades rurales en Panamá.…”
Section: Discussionunclassified